Heterologous expression of the ThIPK2 gene enhances drought resistance of common wheat - Shu-juan ZHANG; Yu-lian LI; Guo-qi SONG; Jie GAO; Rong-zhi ZHANG; Wei LI; Ming-li CHEN; Gen-ying LI (Journal of Integrative Agriculture, 2020)
ThIPK2 is an inositol polyphosphate kinase gene cloned from Thellungiella halophila that participates in diverse cellular processes. Drought is a major limiting factor in wheat (Triticum aestivum L.) production. The present study investigated whether the application of the ThIPK2 gene could increase the drought resistance of transgenic wheat. The codon-optimized ThIPK2 gene was transferred into common wheat through Agrobacterium-mediated transformation driven by either a constitutive maize ubiquitin promoter or a stress-inducible rd29A promoter from Arabidopsis. Molecular characterization confirmed the presence of the foreign gene in the transformed plants. The transgenic expression of ThIPK2 in wheat led to significantly improve drought tolerance compared to that observed in control plants. Compared to the wild type (WT) plants, the transgenic plants showed higher seed germination rates, better developed root systems, a higher relative water content (RWC) and total soluble sugar content, and less cell membrane damage under drought stress conditions. The expression profiles showed different expression patterns with the use of different promoters. The codon-optimized ThIPK2 gene is a candidate gene to enhance wheat drought stress tolerance by genetic engineering.